DETEKSI DINI FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS KEPADATAN MINERAL TULANG PADA WANITA USIA SUBUR DI KOTA PEKANBARU - Rini Hariani Ratih, Salmiati, (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Data from the US National Health Agency (Osteoporosis Foundation) in 1997 estimatedthat about 25 million Americans suffer from osteoporosis, 80% of which is experienced bywomen. Then in the World Conference on Osteoporosis Caring Society in Beijing in 2009,data from 14 Asian countries will show 50% osteoporosis cases by 2050. There are severalrisk factors that cause osteoporosis in women who are divided into two, among otherfactors that can not be controlled by age, sex, genetics, menopause, race, and controlledfactors such as exercise, caffeine and carbon consumption, calcium intake, corticosteroidmedication, smoking, Body Mass Index, and alcohol consumption. Research ObjectivesEarly detection of factors related to bone mineral density status in women of infertile agein Pekanbaru. This research is a quantitative analytic research, with cross sectionalresearch design. Samples in this study were women of childbearing age who are in thework area Kecamatan Tampan as many as 399 people. Analysis with Chi-Square test ofthe relationship between calcium intake on bone mineral density status in women ofchildbearing age with Pvalue 0,000 <Alpha 0,05 with big OR is 922.629 (95% CI:125,039-6807,809) meaning less respondent intake calcium risk 922 times suffering fromosteoporosis. the relationship between caffeine consumption and carbonated beverage tobone mineral density status in women of reproductive age with Pvalue 0,000 <Alpha 0,05with OR is 24,330 (95% CI: 10,174-58,182) means respondents who consume caffeine andcarbonated beverages risk 24 times suffering from osteoporosis.Keywords: Early detection, bone mineral density status, women of childbearing age